BENEFITS OF MUSIC EDUCATION IN PRESCHOOL EDUCATION - Shadiyeva Gavkhar Emindzhanovna (Journals Park Publishing, 2024)
This study explores the multifaceted benefits of introducing music education into preschool education. Within the framework of the structured IMRAD (Introduction, Methods, Results, and Discussion), the study reveals the cognitive, social, emotional, and developmental benefits of early exposure to music in young children. The findings highlight the importance of music education in preschool education for promoting holistic growth and developing key skills that are important for lifelong learning.
Keywords: Music education, preschool education, early childhood development, cognitive abilities, social development, emotional intelligence.